A validity test of capital asset pricing model for Dhaka Stock Exchange - Hasan, Md. Zobaer; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (Asian Network for Scientific Information, 2011)
Capital Asset Pricing Model (CAPM) was a revolution in financial theory. CAPM postulates an equilibrium linear association between expected return and risk of an asset.This study investigates a risk-return relationship within the CAPM framework in Dhaka Stock Exchange (DSE) using monthly stock returns from 80 non-financial companies for the period of January 2005 to December 2009.From the CAPM empirical analysis, it is observed that intercept term is significantly different from zero and insignificant but there exists a positive relationship between beta and share return.The results of the study refute the CAPM hypothesis and offer evidence against the CAPM in DSE market. However, there exists linearity in the securities market line. The unique risk and the interaction are insignificant during the period.